SIFAT ANTIOKSIDAN, KANDUNGAN FENOLAT TOTAL dan FLAVONOID TOTAL EKSTRAK KULIT BATANG MERTAPANG (Terminalia copelandii Elmer) - Tri Murningsih (BERITA BIOLOGI, 2012)
The antioxidant properties of methanolic extract of T. copelandii Elmer bark have been evaluated by using free radical (DPPH) scavenging assay, reduction power and ß-caroten bleaching assay. Ascorbic acid (vitamin C) and “butylated hydroxytoluene” (BHT) were used as positive control or antioxidant standard. Total phenolic content was estimated by using Folin-Ciocalteu reagent and expressed in gallic acid (Gallic Acid Equivalent), while total flavonoid content was estimated by using aluminium chloride reagent and expressed in routine (Routine Equivalent). The result shows antiradical activity of extract on concentration 40 µg/ml was 89.96%, lower than vitamin C (95.61%) but higher than BHT ((52.25%). The reducing power of extract on concentration 50 µg/ml has absorbance value 0.644 lower than vitamin C (0.769), but higher than BHT (0.475). During 2 hours incubation, extract on concentration 50 µg/ml inhibited ß-caroten bleaching 69.46% higher than control negative (35.81%), but lower than BHT (85.99%). Estimation of total phenolic and total flavonoid content showed that extract contained 350.40 µg (GAE)/g extract and 277.50 µg (RE)/g extract respectively. The antioxidant properties may be attributed to the presence of phenolic and flavonoid compounds present in the extract.